Fenomena Intoleransi Antar Umat Beragama Serta Peran Sosial Media Akun Instagram Jaringan Gusdurian Indonesia Dalam Menyampaikan Pesan Toleransi - M. Ardini Khaerun Rijaal (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2021)
In the 20th century, in the midst of the active flow of communication technology, which is increasingly active, it provides many conveniences and benefits to the community, especially when accessing information related to religion and da'wah that anyone wants to access. This phenomenon has an impact on various religious understandings by some sects and religious organizations in Indonesia. As we know, there are some of the largest religious organizations that have existed in this country for a long time, namely, Nahdatul Ulama', Muhammadiyah, etc. With the many religious notions that are studied and embraced by some Indonesians, it gives a lot of influence in understanding the religious concept of difference. This can lead to conflict between communities and religious organizations because they have diverse and different religious understandings. Intolerance is a scourge that is very difficult to eliminate in this democratic country. It is proven by the many cases of intolerance that often occur in our country. In recent years, religious issues have become the object of discussion to cause inter-religious conflicts that are spread through social media. with the existence of the Indonesian Gusdurian Network community, it has a very significant influence in countering and also educating the social media world about tolerance between religious communities. Social media is the main tool to provide education and also the importance of understanding differences in diversity with the spirit of maintaining tolerance between religious communities.